2016
DOI: 10.1007/978-1-4939-4035-6_11
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Stability of mRNAs and Noncoding RNAs

Abstract: Changes in RNA stability have an important impact in the gene expression regulation. Different methods based on the transcription blockage with RNA polymerase inhibitors or metabolic labeling of newly synthesized RNAs have been developed to evaluate RNA decay rates in cultured cell. Combined with techniques to measure transcript abundance genome-wide, these methods have been used to reveal novel features of the eukaryotic transcriptome. The stability of protein-coding mRNAs is in general closely associated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Moreover, we detected that if aspirin treatment affected the mRNA decay of TMEM208 and PQLC2 in colon cancer cells. HCT116 cells were treated with and without 5 mM aspirin for 24 h, and then further treated with 5 μM Dactinomycin D, an inhibitor of RNA polymerase, for 0 h, 0.5 h, 1 h and 2 h respectively [2931]. Finally, the relative ratio of TMEM208 to PQLC2 in cells with aspirin and without aspirin treatment at different time points after Dactinomycin D treatment was calculated respectively, and the result showed that the relative ratio of TMEM208 to PQLC2 was identical in HCT116 cells with and without aspirin treatment at each time point after Dactinomycin D treatment (Figure 6C), which suggests that aspirin treatment does not affect the mRNA decay of TMEM208 and PQLC2.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we detected that if aspirin treatment affected the mRNA decay of TMEM208 and PQLC2 in colon cancer cells. HCT116 cells were treated with and without 5 mM aspirin for 24 h, and then further treated with 5 μM Dactinomycin D, an inhibitor of RNA polymerase, for 0 h, 0.5 h, 1 h and 2 h respectively [2931]. Finally, the relative ratio of TMEM208 to PQLC2 in cells with aspirin and without aspirin treatment at different time points after Dactinomycin D treatment was calculated respectively, and the result showed that the relative ratio of TMEM208 to PQLC2 was identical in HCT116 cells with and without aspirin treatment at each time point after Dactinomycin D treatment (Figure 6C), which suggests that aspirin treatment does not affect the mRNA decay of TMEM208 and PQLC2.…”
Section: Resultsmentioning
confidence: 99%
“…They are more abundant than expected and more stable than linear RNAs due to the covalently closed loop structures, which can resist RNA exonuclease and RNase R activity. In addition, the half-life of stable ncRNAs is about 48 hours, which is much more than that of mRNAs (10 hours) (Ayupe & Reis, 2017).…”
Section: Circrnas As Potential Diagnostic and Prognostic Biomarkers Omentioning
confidence: 99%
“…Natural antisense transcripts, Nats, also called natural antisense RNA, is a complementary transcription product of sense RNA produced in natural organisms, which is transcribed by antisense strand in DNA double strand and processed by RNA polymerase II (RNA polymerase II) [55][56][57][58][59]. NATs can regulate the expression of mRNA and protein at the transcriptional and post-transcriptional levels [60].…”
Section: The Study Of Antisense Long Noncoding Rnasmentioning
confidence: 99%